2019
DOI: 10.1038/s41556-019-0414-2
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of β2 integrins to actin by a mechanosensitive molecular clutch drives complement receptor-mediated phagocytosis

Abstract: αMβ2 integrin (complement receptor 3) is a major receptor for phagocytosis in macrophages. In other contexts, integrins' activities and functions are mechanically linked to actin dynamics through focal adhesions (FAs). We asked whether mechanical coupling of αMβ2 integrin to the actin cytoskeleton mediates phagocytosis. We found that particle internalization was driven by formation of Arp2/3 and formin-dependent actin protrusions that wrapped around the particle. Focal complex-like adhesions formed in the phag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
150
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(159 citation statements)
references
References 81 publications
8
150
1
Order By: Relevance
“…In contrast, early studies by electron microscopy suggested that αMβ2-mediated phagocytosis occurred by sinking of the particle into the cell body (73,74), however, thin protrusions surrounding iC3b-opsonized particles have since been observed by electron microscopy (31,75,76). Moreover, three-dimensional live cell microscopy revealed the formation of actin-based membrane protrusions in all the observed phagocytic events of iC3b-opsonized particles (77). Thus, formation of actin-based protrusions that extend along the target appears to be a defining feature of phagocytosis, independent of the receptor.…”
Section: Actin-based Protrusion Is a General Feature Of Phagocytosismentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, early studies by electron microscopy suggested that αMβ2-mediated phagocytosis occurred by sinking of the particle into the cell body (73,74), however, thin protrusions surrounding iC3b-opsonized particles have since been observed by electron microscopy (31,75,76). Moreover, three-dimensional live cell microscopy revealed the formation of actin-based membrane protrusions in all the observed phagocytic events of iC3b-opsonized particles (77). Thus, formation of actin-based protrusions that extend along the target appears to be a defining feature of phagocytosis, independent of the receptor.…”
Section: Actin-based Protrusion Is a General Feature Of Phagocytosismentioning
confidence: 88%
“…The lamellipodium is followed by a less dynamic and thicker region called the lamella, where actin cross-linking proteins and non-muscle myosin II motors organize the actin network into contractile bundles (85)(86)(87). Similar to lamellipodia, the Arp2/3 complex is implicated in both FcγR and αMβ2-mediated phagocytosis (31,77,88). Live cell SIM-TIRF microscopy of filamentous actin (F-actin) during the formation of a frustrated phagocytic cup upon engagement of αMβ2 suggests the formation of a branched actin network, with Arp2/3 localized at the leading edge, similar to a lamellipodium (77).…”
Section: Comparison Of the Actin Organization In Migrating Cells Andmentioning
confidence: 99%
“…We also show that Arp2/3 inhibition impairs cell motility and phagocytosis, while inhibiting formin-derived contractile networks with SMIFH2 impairs directional persistence. Because Arp2/3-derived networks also promote lamellar protrusions, α-motility, and phagocytosis in opisthokonts and amoebozoans (Davidson et al, 2018;Jaumouille et al, 2019;Seastone et al, 2001;Veltman et al, 2012;Veltman et al, 2016), our results suggest that the Arp2/3dependent mechanisms that drive motility and phagocytosis are evolutionarily ancient, and can function independently of a microtubule cytoskeleton.…”
Section: Discussionmentioning
confidence: 56%
“…In diverse cell types including Dictyostelium amoebae and mammalian leukocytes, the actin networks that promote the assembly of lamellar pseudopods also promote phagocytosis (Davidson et al, 2018;Jaumouille et al, 2019;Seastone et al, 2001;Veltman et al, 2012;Veltman et al, 2016). To test the hypothesis that Arp2/3-dependent actin networks drive phagocytosis as well as cell motility in Naegleria, we treated cells with LatB or CK-666 and incubated cells with GFP-expressing bacteria.…”
Section: Phagocytosis Requires Actin Assembly and Is Enhanced By Arpmentioning
confidence: 99%
See 1 more Smart Citation